[quotation] On partnership - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On partnership: 'Partnership does not imply an automatic right to expect, or responsibility to give, massive financial assistance for projects. Partnership schemes are conceived as an interchange of ideas, information, problems and methods of...